2004
DOI: 10.1073/pnas.0404278101
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone activates mitogen-activated protein kinase and the cAMP response element binding protein transcription factor in Sertoli cells

Abstract: The androgen testosterone is essential for the Sertoli cell to support the maturation of male germ cells and the production of spermatozoa (spermatogenesis). In the classical view of androgen action, binding of androgen to the intracellular androgen receptor (AR) produces a conformational change in AR such that the receptor-steroid complex has high affinity for specific DNA regulatory elements and is able to stimulate gene transcription. Here, we demonstrate that testosterone can act by means of an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 68 publications
6
113
4
Order By: Relevance
“…DHT did not activate MAPK3/1 or PI3K/AKT signalling pathways in hamster Leydig cells (results not shown). Although testosterone failed to activate PI3K/AKT (results not shown), this androgen induced a rapid phosphorylation of MAPK3/1 within short-term incubations (1-3 min), which was also detected after 2-3 h. These results are similar to those observed in studies performed in breast cancer, skeletal muscle cells, prostate stroma cells and Sertoli cells in which androgen activates MAPK3/1 too quickly to be explained by the classical androgen receptor pathway (Peterziel et al 1999, Zhu et al 1999, Estrada et al 2003, Fix et al 2004, Rahman & Christian 2007. We also found that Bi prevented the effects of testosterone on phospho-MAPK3/1 indicating that androgen receptors are required for testosterone-mediated MAPK activation.…”
Section: Testosterone Induces Testicular Ptgs2supporting
confidence: 80%
See 1 more Smart Citation
“…DHT did not activate MAPK3/1 or PI3K/AKT signalling pathways in hamster Leydig cells (results not shown). Although testosterone failed to activate PI3K/AKT (results not shown), this androgen induced a rapid phosphorylation of MAPK3/1 within short-term incubations (1-3 min), which was also detected after 2-3 h. These results are similar to those observed in studies performed in breast cancer, skeletal muscle cells, prostate stroma cells and Sertoli cells in which androgen activates MAPK3/1 too quickly to be explained by the classical androgen receptor pathway (Peterziel et al 1999, Zhu et al 1999, Estrada et al 2003, Fix et al 2004, Rahman & Christian 2007. We also found that Bi prevented the effects of testosterone on phospho-MAPK3/1 indicating that androgen receptors are required for testosterone-mediated MAPK activation.…”
Section: Testosterone Induces Testicular Ptgs2supporting
confidence: 80%
“…Moreover, testosterone and/or DHT effects could take place through non-classical mechanisms. It has been recently reported the activation of the MAP kinase pathway and the phosphoinositide-3 (PI3) kinase/serine threonine kinase AKT signalling cascade by androgens in Sertoli, prostate and osteoblast cells (Fix et al 2004, Kang et al 2004, Chen et al 2007, Cinar et al 2007, Pinthus et al 2007, Rahman & Christian 2007, Agoulnik et al 2008. As a consequence, we have investigated the participation of those signalling pathways in the regulation of PTGS2 expression by testosterone and DHT in hamster Leydig cells.…”
Section: Testosterone Induces Testicular Ptgs2mentioning
confidence: 99%
“…This compromises Sertoli-germ cell adhesion without affecting blood-testis barrier dynamics. Moreover, the importance of ERK in the testis is supported by another study, which demonstrated that testosterone can mediate its effects on Sertoli-germ cell adhesion via the Src-ERK signaling cascade instead of the classic androgen receptor-mediated pathway (Fix et al, 2004). Indeed, testosterone is known to play a critical function in the regulation of the blood-testis barrier and anchoring junctions in the testis (O'Donnell et al, 2000;Meng et al, 2005).…”
Section: Cytokines and Growth Factorsmentioning
confidence: 96%
“…In neurons, CREB activation is known to regulate a variety of neurotrophic and neuroprotective effects (Crino et al, 1998;Finkbeiner, 2000;Kelly et al, 2000). It is not known whether androgens activate CREB in neurons, although androgens have been shown to activate CREB signaling in nonneural cells (Fix et al, 2004;Unni et al, 2004;Walker, 2003). In fact, androgen-induced, ARdependent MAPK/ERK-CREB signaling in prostate cancer cells attenuates apoptosis (Kousteni et al, 2003).…”
Section: Androgen Activation Of Creb Signalingmentioning
confidence: 99%